Analysis Of The Effect Of Employee Readiness On The Implementation Of Accreditation At Royal Prima Medan Rsu - Muhammad Asyraf; Marlinang Isabella Silalahi; Sri Lestari Ramadhani; Sri Ulina Karo-karo (International Journal of Health and Pharmaceutical (IJHP), 2022)
Hospitals are required to carry out accreditation to improve the quality of health services, some employees feel accreditation is a workload and they are not ready to carry out the sustainability of hospital accreditation. The purpose of this study was to analyze the relationship between employee readiness and the sustainability of hospital accreditation. This research is an analytic study with a cross-sectional approach. The study was conducted at Royal Prima Hospital Medan. The study population was 230 people and a sample of 70 people. Sampling by stratified random sampling. Data analysis used univariate, bivariate with chi-square test, and multivariate with multiple logistic regression at the 95% confidence readiness to change, management support, and self-benefit with the continuation of hospital accreditation at the Royal Prima Hospital in Medan, p <0.05. While the unrelated variable is confidence, p> 0.05. The variable that has the greatest relationship with the sustainability of hospital accreditation is management support with the value Exp (B) / OR = 18.978. The management of Royal Prima Hospital needs to continue to support the improvement of the quality and professionalism of employees with continuing education and training to improve the quality and safety of patients at Royal Prima Hospital Medan.